Angiogenic imbalance in pregnancies with preterm prelabor rupture of membranes between 34 and 37 weeks of gestation - Marian Kacerovsky; Helena Hornychova; Sunil Jaiman; Ladislava Pavlikova; Magdalena Holeckova; Bo Jacobsson; Panagiotis Tsiartas; Ivana Musilova (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study aimed to identify whether microbial invasion of the amniotic cavity and/or intra‐amniotic inflammation in women with late preterm prelabor rupture of membranes (PPROM) was associated with changes in concentrations of soluble fms‐like tyrosine kinase‐1 (sFlt‐1), placental growth factor (PlGF) and its ratio in maternal serum, and whether placental features consistent with maternal vascular malperfusion further affect their concentrations. Material and methods This historical study included 154 women with singleton pregnancies complicated by PPROM between gestational ages 34+0 and 36+6 weeks. Transabdominal amniocentesis was performed as part of standard clinical management to evaluate the intra‐amniotic environment. Women were categorized into two subgroups based on the presence of microorganisms and/or their nucleic acids in amniotic fluid (determined by culturing and molecular biology method) and intra‐amniotic inflammation (by amniotic fluid interleukin‐6 concentration evaluation): (1) those with the presence of microorganisms and/or inflammation (at least one present) and (2) those with negative amniotic fluid for infection/inflammation (absence of both). Concentrations of sFlt‐1 and PlGF were assessed using the Elecsys® sFlt‐1 and Elecsys® PlGF immunoassays and converted into multiples of medians. Results Women with the presence of microorganisms and/or inflammation in amniotic fluid had lower serum concentrations of sFlt‐1 and sFlt‐1/PlGF ratios and higher concentrations of PlGF compared with those with negative amniotic fluid. (sFlt‐1: presence: median 1.0 multiples of the median (MoM), vs negative: median: 1.5 MoM, P = 0.003; PlGF: presence: median 0.7 MoM, vs negative: median 0.4 MoM, P = 0.02; sFlt‐1/PlGF: presence: median 8.9 vs negative 25.0, P = 0.001). Higher serum concentrations of sFlt‐1 and sFlt‐1/PlGF ratios as well as lower concentrations of PlGF were found in the subsets of women with maternal vascular malperfusion than in those without maternal vascular malperfusion. Conclusions Among women experiencing late PPROM, angiogenic imbalance in maternal serum is primarily observed in those without both microbial invasion of the amniotic cavity and intra‐amniotic inflammation. Additionally, there is an association between angiogenic imbalance and the presence of maternal vascular malperfusion.